Comparison of Perioperative Outcomes between the Supraclavicular Artery Island Flap and Fasciocutaneous Free Flap. (14th October 2015) - Kozin, Elliott D.; Sethi, Rosh K.; Herr, Marc; Shrime, Mark G.; Rocco, James W.; Lin, Derrick; Deschler, Daniel G.; Emerick, Kevin S.
Abstract : Objective: Outcomes of the supraclavicular artery island flap (SCAIF) have not been extensively studied in comparison with free tissue transfer (FTT) flaps for head and neck reconstruction. We hypothesize that the pedicled SCAIF has decreased operating room time, length of stay, time to wound healing of recipient site, complications, and hospital charges as compared with FTT. Study Design: Case series with chart review. Setting: Tertiary care teaching hospital. Subjects and Methods: Medical records were reviewed for patients who underwent SCAIF (n = 45) or FTT (n = 28) reconstruction between 2011 and 2013. Results: Total operating room time was significantly lower for the SCAIF group vs the FTT group (6.7 vs 8.1 hours, P =. 002). Procedural time was 5.7 hours for the SCAIF group, as compared with 7.2 hours for FTT group ( P =. 0015). Mean area for SCAIF donor site was 63.89 cm 2 vs 81.8 cm 2 for the radial forearm free flap group ( P =. 015). There was no significant difference in mean length of stay between SCAIF (8.8 days) and FTT (11 days, P =. 12). Mean length of time to wound healing of the recipient site was similar in the SCAIF group vs the FTT group (17.3 vs 22.1 days, P =. 071). Ratio of total hospital charges for SCAIF were 32% lower than that of FTT ( P =. 0001). Conclusion: This is among the first studies to compare SCAIF with FTT in a large cohort analysis. We find decreased operating room times for SCAIF vs FTT, with similar length of stay and wound healing. Other outcomes between SCAIF and FTT were also comparable.